De micronutrientes a elementos potencialmente tóxicos: crescimento e produção de biomassa de Canavalia ensiformis e Leucaena leucocephala em resposta ao excesso de Cu e Fe no solo - Bomfim, Nayane Cristina Pires [UNESP] (Universidade Estadual Paulista (Unesp), 2024)
The increase in potentially toxic elements (PTEs) in the soil is worrying, especially in agricultural soils due to the bioaccumulation factor. Copper (Cu) and iron (Fe) are micronutrients, responsible for important functions in the plant body, but the high availability of these elements in the soil can cause soil contamination and toxicity in plants. Canavalia ensiformis and Leucaena leucocephala have been the target of studies that explore their tolerance and phytoremediation potential to some PTEs, and the focus of this study is to understand the physiological responses (gas exchange, growth, tolerance, biomass, accumulation, translocation) of these species to high Cu and Fe contents in the soil, separately, and evaluate the growth of L. leucocephala in excess of these elements in the soil for 12 and 24 months of cultivation (long-term cultivation) in a greenhouse. Treatments 50, 150, 250 and 350 mg dm-3 of each element (CuSO4*5H2O and FeSO4*7H2O), separately, were incorporated into the soil (Oxisol) of each experimental unit (six replications per treatment), in addition to the control. Seeds of C. ensiformis and L. leucocephala were sown in the soil enriched with the treatments in pots of 4 and 10 dm3 of soil, respectively and after emergence they were cultivated in a greenhouse for 90 days (C. ensiformis); 12 and 24 months (L. leucocephala) in a completely randomized design. Biometric assessments (length, diameter) gas exchange was performed; fresh and dry weight of the organs (roots, leaves and stems), quantification of Cu and Fe in plant organs and quantification of the bioavailability of the elements in the soil. Based on these data, calculations of tolerance, accumulation and translocation were carried out. C. ensiformis was tolerant to Fe treatments and as for Cu, it showed tolerance up to treatment 150 mg dm-3. The tolerance of the species is dependent on chlorophyll levels and gas exchange. There was accumulation of both PTEs in the roots and translocation to the shoot. L. leucocephala showed tolerance to Cu and Fe up to treatment 50 and 250 mg dm-3, respectively, at both cultivation times. The time of exposure to PTE negatively influenced the biomass of L. leucocephala subjected to Cu, unlike Fe. L. leucocephala accumulated more Cu over time, the same did not happen for plants subjected to Fe.

O aumento de elementos potencialmente tóxicos (EPTs) no solo é preocupante, principalmente em solos agrícolas devido ao fator de bioacumulação. Cobre (Cu) e ferro (Fe) são micronutrientes, responsáveis por importantes funções no corpo vegetal, mas a alta disponibilidade desses elementos no solo podem causar contaminação do solo e toxicidade nas plantas. Canavalia ensiformis e Leucaena leucocephala tem sido alvo de estudos que exploram seu potencial de tolerância e fitorremediação a alguns EPTs, e o foco deste estudo é compreender as respostas fisiológicas (trocas gasosas, crescimento, tolerância, biomassa, acúmulo, translocação) destas espécies a elevados teores de Cu e Fe no solo, separadamente, e avaliar o crescimento de L. leucocephala ao excesso destes elementos no solo por 12 e 24 meses de cultivo (cultivo a longo prazo) em casa de vegetação. Os tratamentos 50, 150, 250 e 350 mg dm-3 de cada elemento (CuSO4*5H2O e FeSO4*7H2O), separadamente, foi incorporado ao solo (Oxisol) de cada unidade experimental (seis repetições por tratamento), além do controle. Sementes de C. ensiformis e L. leucocephala foram semeadas no solo enriquecido com os tratamentos em vasos de 4 e 10 dm3 de solo, respectivamente e após a emergência foram cultivadas em casa de vegetação por 90 dias (C. ensiformis); 12 e 24 meses (L. leucocephala) em delineamento inteiramente casualisado. Foram feitas avaliações biométricas (comprimento, diâmetro) trocas gasosas; peso fresco e seco dos órgãos (raiz, folhas e caules), quantificação de Cu e Fe nos órgãos das plantas e quantificação da biodisponibilidade dos elementos no solo, a partir desses dados os cálculos de tolerância, acúmulo e translocação foram realizados. C. ensiformis foi tolerante aos tratamentos de Fe e quanto ao Cu, apresentou tolerância até o tratamento 150 mg dm-3. A tolerância da espécie é dependente aos teores de clorofilas e trocas gasosas. Houve acúmulo de ambos os EPTs nas raízes e translocação para a parte aérea. L. leucocephala apresentou tolerância ao Cu e ao Fe até o tratamento 50 e 250 mg dm-3, respectivamente, em ambos os tempos de cultivo. O tempo de exposição ao EPT influenciou negativamente a biomassa de L. leucocephala submetidas ao Cu, diferentemente do Fe. L. leucocephala acumulou mais Cu ao longo do tempo, já o mesmo não aconteceu para as plantas submetidas ao Fe.
From micronutrients to potentially toxic elements: growth and biomass production of Canavalia ensiformis and Leucena leucocephala in response to excessive cu and fe in the soil
Keywords: Tolerância; Biomassa; Toxicidade; Leguminosa; Acúmulo; Translocação; Tolerance; Biomass; Toxicity; Legumes; Accumulation; Translocation